Measurements Optimization for Control of Distributed Parameter Systems - Brodsky, Sergey A.; Nebylov, Alexander V.; Panferov, Alexander I. (2018 5th IEEE International Workshop on Metrology for AeroSpace (MetroAeroSpace), 2018)
The problem of measurements optimization for control of system with distributed parameters is discussed. An approach based on a modal representation of the plant with distributed parameters is considered. The limitations for the maximum permissible error of estimates of the controlled variables and for the time-averaged values of the used criteria of control quality are presented by a set of linear matrix inequalities of problem optimization of the sensor and control loads. Minimizing of the objective function associated with position and parameters of sensors is a subject to restrictions satisfies to minimal measurement costs and determines the required number, parameters and locations of sensors.